Antibacterial properties of crude aqueous Hylocereus polyrhizus peel extracts in lipstick formulation against gram-positive and negative bacteria - Asrul Afandi,; Azwan Mat Lazim,; Azwanida N.N.,; Mumtaz Abu Bakar,; Othman Airianah,; Shazrul Fazry, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Development of natural formulated lipstick using natural bio resources namely plant pigments and essential oils was carried out as an alternative to chemical-based ingredients due to their side effects and damages to health. Hylocereus polyrhizus (Costa Rican Pitahaya, also more popularly known among Malaysian as “Dragon Fruit”) peels are normally treated as wastes and will be discarded during processing. In this study, the peel extracts were used in the lipstick formulation as a natural colorant. The antibacterial activity of the formulation against six pathogens was evaluated using disc diffusion method and broth micro-dilution method. The observation from disc diffusion method showed that extracts and formulated lipstick from H. polyrhizus were able to inhibit the growth of Escherichia coli, Klebsiella pneumonia, Salmonella typhimurium, Staphylococcus aureus, and Enterococcus faecalis. The observation from the minimum inhibitory concentration (MIC) showed that all extracts inhibit the growth of bacteria in the range of 1.00-7.00 mg/mL for all bacteria while their minimum bactericidal concentrations (MBC) indicated double of the MIC concentration except for B. cereus, which shows very high resistance toward the extract. Even though there is no clear trend indicating which bacteria were sensitive most to the extract, it can be concluded that the water extract of H. polyrhizus peel showed potent antibacterial activity. Essential oils from H. polyrhizus flower and the combination of virgin coconut and olive oil that were added to the products for flavors and aroma have the potential as preservative due to their antibacterial properties. With the incorporation of natural ingredients, the lipstick is considered as a safe and attractive product, with multi-functional uses namely to prevent chapped lips, freshen the breath, reduces mouth odor and contributes in improving general health quality.